Prebiotic properties of crude oligosaccharide prepared from enzymatic hydrolysis of basil seed gum - Pairote Wongputtisin (2018)
© 2015, The Korean Society of Food Science and Technology and Springer Science+Business Media Dordrecht. Novel prebiotic was prepared from basil seed gum (Ocimum basilicum) using Thermoascus aurantiacus endo-xylanase. Crude basil oligosaccharide was produced and tested for prebiotic properties (in vitro and in vivo). Growth of Pediococcus acidilactici and Enterococcus faecium was stimulated in medium containing 1% (w/v) basil oligosaccharide comparing to glucose as a carbon source. In contrast, growth of Salmonella Havana and Escherichia coli was not stimulated by this oligosaccharide. Total lactic acid bacteria (LAB) in human fecal slurry was increased when 1% (w/v) of basil oligosaccharide was supplemented, while Salmonella-Shigella spp. group decreased (p<0.05). Daily administration (3 weeks) of 150 mg crude oligosaccharide to Wistar rats increased fecal LAB but non-significant (p>0.05), while Salmonella-Shigella spp. significantly (p<0.05) decreased. Thus, crude oligosaccharide prepared by enzymatic hydrolysis of basil seed gum may be useful as prebiotic for human foods.